PENGARUH GDP JEPANG, KURS YEN, DAN IMPLEMENTASI IJEPA TERHADAP NILAI EKSPOR KARET INDONESIA KE JEPANG - Narawinda, Anak Agung Sagung Diah Suta; Ayuningsasi, Anak Agung Ketut (Buletin Studi Ekonomi; VOLUME.28.NO.02.TAHUN.2023, 2023)
Indonesia is a country that is supported by the availability of excellent and diverse natural resource potential. Rubber is one of the natural products that contribute the highest foreign exchange in Indonesia. Rubber opens up great opportunities for Indonesia to export to developed countries such as Japan which is known for its sophisticated technology. Therefore, this study aims to determine the effect of Japan's GDP, the Yen exchange rate, and the implementation of the IJEPA cooperation on the value of Indonesian rubber exports to Japan within 24 years. The data used is secondary data obtained through UN Comtrade, World Bank, and Bank Indonesia with the type of data used being time series. The method used in this study is the Error Correction Model. The results showed that Japan's GDP and IJEPA implementation had a positive and significant effect on the value of Indonesian rubber exports to Japan, while the Yen exchange rate had a negative and insignificant effect on the value of Indonesian rubber exports to Japan.